The acute effect of self-induced unclassified therapeutic tremors on cardiac autonomi responses and interictal state anxiety symptoms in individuals with epilepsy - Botha, Annette Jacolien (Stellenbosch : Stellenbosch University, 2022)
Thesis (M Sport Sc)-Stellenbosch University, 2022.